1990
DOI: 10.1111/j.1365-2133.1990.tb08292.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermolytic hyperkeratosis: generalized form in children from parents with systematized linear form

Abstract: Two unrelated families are presented in both of which a child with generalized epidermolytic hyperkeratosis (congenital bullous ichthyosiform erythroderma) had a parent with linear epidermolytic hyperkeratosis (epidermolytic epidermal naevus). Light and electron microscopy of skin biopsies of lesions from the children and parents showed typical epidermolytic hyperkeratosis. Gonadal mosaicism in patients with linear epidermolytic hyperkeratosis may be responsible for transmission of the abnormality to the offsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 12 publications
1
31
0
2
Order By: Relevance
“…Later it was reported that patients with a segmental manifestation of an autosomal dominant skin disease had an increased risk of transmitting the trait in the ordinary, nonsegmental form to their children (16,17). Such observations implied that the underlying mutation could also affect the germline in the form of gonadal mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…Later it was reported that patients with a segmental manifestation of an autosomal dominant skin disease had an increased risk of transmitting the trait in the ordinary, nonsegmental form to their children (16,17). Such observations implied that the underlying mutation could also affect the germline in the form of gonadal mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…[72][73][74] Because recognition of this risk is important for genetic counseling, epidermolytic nevi have been included (in brackets) in the classification of KPI (Table II).…”
Section: Classification Of the Keratinopathic Ichthyosesmentioning
confidence: 99%
“…2,3 It is known that the offspring of patients with an epidermolytic-type of epidermal nevi may have generalized BCIE. 4,5 Paller et al 6 and Moss et al 7 showed that epidermal nevus represents somatic mosaicism for a keratin 10 gene mutation, which may produce generalized BCIE in the next generation if germline cells carry the mutation. Although theoretically a possibility, keratin 1 gene mosaicism has not yet been described as a cause of epidermal nevi.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Recently, Paller et al 6 demonstrated the same keratin gene mutations in the lesional keratinocytes of the epidermal nevi of parents and in the DNA of their offspring with BCIE. These results provide evidence that a postzygotic mutation can be passed on to the next generation in BCIE.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation